Preschool Leaders as Enablers of Innovation: Emerging practices with preschool leaders in Vietnam. Issue 2 (4th March 2019) - Leroy, Lieve; Nguyen, Thi Chau
Abstract : Context has a significant impact on the relative success of efforts to innovate in the classroom. Thus, it is important to understand the role of school leaders as both gatekeepers and facilitators within their specific context.